TINGKAT BEBAN KERJA PERAJIN GAMELAN BALI - Juli Suarbawa, I Ketut Gde; ., Nyoman Adiputra; Sutjana, I Dewa; ., Ketut Tirtayasa (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic), 2016)
The production process of making gamelan in the village Tihingan, Klungkung, Bali, still using the traditional fireplace with open flames both to the melting process as well as on the process of formation so that crafters fairly heavy workload caused by exposure to radiation heat and dust. This research was conducted observational against 5 people workers (craftsman) gamelan nguwad process. The workload is measured by pulse craftsman work. Microclimate in the workplace were measured wet temperature, dry temperature, humidity, intensity of noise, and light intensity. Musculoskeletal disorderpredicted by questioner of Nordic Body Map and general fatigue  predicted  by  the questioner 30 items exhaustion with four Likert scale. The results of the research to get the pulse of gamelan craftsmen working on a furnace repairman 116.25 ± 3.78, the flop workers 115.42 ± 2.47, and 3.29 ± 126.47 of nguwad workers. The cardio vasculer load obtained 50.13 ± 3.42% so the recommended 75% work and 25% rest. Gamelan making production process also cause a variety of subjective disorders. It was concluded that (a) the level of workload on a craftsman gamelan is the artisan perapen and artisan-flops belonging to the workload being, the artisan nguwad workload is quite heavy, (b) based on the value of CVL, workload craftsman gamelan in Bali including the workload being, ( c) a significant increase in musculoskeletal disorder and general fatigue. To overcome this condition it is recommended that the working process of making gamelan remedied through the implementing appropriate technology and ergonomics intervention.
Keywords: Craftsman gamelan, workload, musculoskeletal disorder, general fatigue